Correlation between Antimicrobial, Antioxidant Activity, and Polyphenols of Alkalized/Nonalkalized Cocoa Powders. Issue 4 (8th March 2017) - Todorovic, Vanja; Milenkovic, Marina; Vidovic, Bojana; Todorovic, Zoran; Sobajic, Sladjana
Abstract: Many factors can influence antioxidative and antimicrobial characteristics of plant materials. The quality of cocoa as functional food ingredient is influenced through its processing. The main aim of this study was to test if there is difference in polyphenol content, antioxidant capacity, and antimicrobial activity between nonalkalized and alkalized cocoa powders. To estimate polyphenol and flavonoid content in cocoa samples the spectrophotometric microassays were used. Flavan‐3ols were determined with reversed‐phase high‐performance liquid chromatography (RP‐HPLC). Antimicrobial activity against 3 Gram positive bacteria, 4 Gram negative bacteria and 1 strain of yeast was determined using broth microdilution method. Total polyphenol content was 1.8 times lower in alkalized cocoa samples than in natural ones. Epicatechin/catechin ratio was changed due to the process of alkalization in favor of catechin (2.21 in natural and 1.45 in alkalized cocoa powders). Combined results of 3 antioxidative tests (DPPH, FRAP, ABTS) were used for calculation of RACI (Relative Antioxidant Capacity Index) and GAS (Global Antioxidant Score) values that were consistently higher in natural than in alkalized cocoa extracts. Obtained results have shown significant correlations between these values and phenolic content (0.929 ≤ r ≤ 0.957, P < 0.01). Antimicrobial activity varied from 5.0 to 25.0 mg/ml (MICs), while Candida albicans was the most sensitive tested microorganism. Cocoa powders subjected to alkalization had significantly reduced content of total and specific phenolic compounds and reduced antioxidant capacity ( P < 0.05), but their antimicrobial activity was equal for Gram‐positive bacteria or even significantly enhanced for Gram‐negative bacteria .